The Urgency of Learning English For Gen Z: A Conceptual Framework in The Era of Digital Transformation - Aisyah Amini Zahara; Aisyah Karlina; Desi Desi; Fadiyah Naila; Nurul As-Syifa Hayati; Susan Elinda (Jurnal Ilmiah Profesi Pendidikan, 2026)
The rapid development of digital transformation has significantly increased the urgency of learning English, especially for Generation Z as digital natives. English is not only a global communication tool but also an essential skill for accessing information, education, and career opportunities in the digital era. This study aims to explore the importance of English proficiency for Generation Z and to develop a conceptual framework that integrates language skills with digital literacy in the modern era. This research uses a qualitative approach through a library research method by analyzing and synthesizing relevant scholarly sources related to English learning, digital transformation, and the characteristics of Generation Z. Data were collected through document analysis of journals, books, and academic articles, and then analyzed using descriptive qualitative techniques. The findings reveal that English plays a crucial role as a global communication tool that enables Generation Z to access information, engage in cross-cultural communication, and improve academic and professional opportunities. In addition, digital literacy and English proficiency are interrelated competencies that are essential for navigating the digital world. However, high exposure to digital content does not automatically guarantee strong English mastery, indicating the need for structured and integrated learning approaches. In conclusion, this study proposes the development of a conceptual framework that integrates English learning and digital skills to prepare Generation Z for global challenges in the era of digital transformation.